Beyond the Labour Income Tax Wedge: The Unemployment-Reducing Effect of Tax Progressivity - Etienne Lehmann; Claudio Lucifora; Simone Moriconi; Bruno Van der Linden (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper argues that, for a given overall level of labour income taxation, a more progressive tax schedule reduces the unemployment rate and increases the employment rate. From a theoretical point of view, higher progressivity induces a wage-moderation effect and increases overall employment since employment of low-paid workers is more responsive. We test these theoretical predictions on a panel of 21 OECD countries over 1998-2008. Controlling for the burden of taxation at the average wage, we show that a more progressive taxation reduces the unemployment rate and increases the employment rate. These findings are confirmed when we account for the potential endogeneity of both average taxation and progressivity. Overall our results suggest that policy-makers should not only focus on the detrimental effects of tax progressivity on in-work effort.
Keywords: E24; H22; J68; 330; wage moderation; employment; taxation